One major river flowing through Bekasi City is Bekasi river. Total extent of the Bekasi watershed is about 39.045 ha, in 2002 with rainfall of 250 mm for 8 hours caused about 138 ha flooded in residents area for 2-3 days in Bekasi City, more extremely in 2005 with rainfall only 127 mm for 6 hours caused about 164 ha flooded in residents area for 3 days. This evidence showed that flood problem in Bekasi City is become worse, and seem to be more horrifying in the future. Therefore, the flood pro - Trihono Kadri; Naik Sinukaban; Hidayat Pawitan; Suria Darma Tarigan (Forum Pasca Sarjana, 2011)
One major river flowing through Bekasi City is Bekasi river. Total extent of the Bekasi watershed is about 39.045 ha, in 2002 with rainfall of 250 mm for 8 hours caused about 138 ha flooded in residents area for 2-3 days in Bekasi City, more extremely in 2005 with rainfall only 127 mm  for 6 hours caused about 164 ha flooded in residents area for 3 days.  This evidence showed that flood problem in Bekasi City is become worse, and seem to be more horrifying in the future. Therefore, the flood problem needs an extremely great attention.  The objectives of the research is (1) analysis watershed condition; (2) analysis of the causes of flood over Bekasi City from the perpective of hydrology and hydraulic; (3) plan of Bekasi watershed management to reduce flood risk in Bekasi City.  To obtain the purposes of this research, the method of analysis is devided into four main subjects: (1) analysis of watershed condition using SCS method; (2) hydrology analysis using hydrology modeling HEC-HMS; (3) river flow capacity using hydraulic modeling HEC-RAS and (4) plan of scenarios to reduce flood risk.  There are four scenarios to overcome the flood problems: (1) similarly with government plan 2010;(2) managing Bekasi watershed area with conservation tillage; (3) build water retarded structure entire of  watershed and;(4) combination of second and third scenarios.  The research results shown that river flow capacity only 462 m3/s is not enough to flow the discharges, otherwise the land use is change and increasing the run off in upstream.  Based on the problems, it is expected to overcome the flood problem by managing Bekasi watershed area with conservation tillage and build water retarded structure.  It will reduce 28.58% of the discharge run off in 2020.   Key words: flood, land use changing, watershed management